(untitled) (Research in Agriculture Livestock and Fisheries, 2023)
Nowadays, Information and Communication Technologies (ICT) are playing important role in communicating agricultural information. In this connection, the government of Bangladesh established a number of Agricultural Information and Communication Centers (AICC) at the Union level to disseminate agricultural information. The purposes of the study were to determine the effectiveness of AICC for disseminating agricultural information and to explore the contribution of the selected characteristics of the AICC member farmers to the effectiveness of AICC. Data were collected from 90 randomly selected farmers of nine Upazillas of Faridpur district under Dhaka division. Face-to-face interview followed by pretested structured questionnaire was held with the selected farmers to gather data. The survey revealed that an overwhelming majority (80%) of the farmers perceived medium effectiveness of AICC, while 7.8% of them perceived low and 12.2% of them perceived high effectiveness of AICC for disseminating agricultural information. The effectiveness of AICC was influenced by the intensity of use of ICT, length of experience to use ICT and ICT using confidence. Therefore, responsible organizations such as Agriculture Information Service (AIS) with the help of the Department of Agricultural Extension (DAE) and other advisory service-providing organizations should take action to enhance the effectiveness of AICC. Vol. 9, No. 3, December 2022: 259-265